LB0002 Does Adding Azathioprine To Glucocorticoid Induction Increase The Remission Rate and Prevent Relapses in Patients with Systemic Necrotizing Vasculitides without Poor-Prognosis Factors? A Multicenter, Double-Blind Randomized Controlled Trial. (15th July 2016) - Puéchal, X.; Pagnoux, C.; Baron, G.; Quémeneur, T.; Néel, A.; Agard, C.; Lifermann, F.; Liozon, E.; Ruivard, M.; Godmer, P.; Limal, N.; Mékinian, A.; et al.
Abstract : Background: Glucocorticoids (GC) achieve remission in most patients with systemic necrotizing vasculitides (SNVs) without poor-prognosis factors based on the 1996 Five-Factor Score. However, more than a third of them relapse, mainly during the first 2 years after treatment onset. Objectives: This study aimed to determine whether combined GC and azathioprine (AZA) could achieve higher remission and lower relapse rates than GC alone in patients with newly diagnosed eosinophilic granulomatosis with polyangiitis (EGPA), microscopic polyangiitis (MPA) or polyarteritis nodosa (PAN), without increasing adverse events. Methods: All patients included in this multicenter, randomized, double-blind trial received GC, initially 1 mg/kg/day, then gradually tapered over 12 months (asthmatic patients' doses were lowered as much as possible while controlling asthma symptoms) and were randomly assigned to receive concomitant 12 months of oral AZA (2 mg/kg/day) or placebo. Patients were followed for another 12 months, for 24 months of follow-up. The primary endpoint was rate of remission without subsequent relapses at month (M) 24. Analyses used a modified intent-to-treat strategy and were adjusted according to the vasculitis. Results: 95 patients (51 EGPA, 25 MPA, 19 PAN) met the inclusion criteria and received at least 1 dose of AZA (n=46) or placebo (n=49). At endpoint, 52.2% AZA-arm patients achieved remission without subsequent relapse versus 51.0% placebo recipients (odds ratio [OR], 0.93; [95% CI, 0.40–2.17]). Secondary endpoints were also comparable between arms: remission rate (95.7% vs. 87.8%), number of patients with minor (30.2% vs. 28.5%) or major relapses (11.6% vs. 11.9%). Two (4.1%) AZA-arm patients died both at M11 (1 sudden death while in complete remission, 1 86-year-old died of congestive heart failure). Mean GC doses and area under the curve for GC use were also comparable between arms. At least 1 severe treatment-related adverse event occurred in 8 (17.4%) AZA-arm and 3 (6.1%) placebo-arm patients (OR, 3.23 [0.76–13.70]). For EGPA patients, neither the primary endpoint nor the numbers with exacerbated asthma/rhinosinusal disease differed between arms. Conclusions: At study M24, AZA adjunction to GC induction compared to GC alone in non-severe SNVs did not improve remission rate or lower the risk of relapse, had no steroid-sparing effect, or did not reduce EGPA patients' rate of asthma/rhinosinusal disease exacerbations. Acknowledgement: CHUSPAN2 trial was funded by French Ministry of Health PHRC P060243 and sponsored by AP–HP; ClinicalTrials.gov number, NCT00647166 . Disclosure of Interest: None declared